Regulação da explosão oxidativa, qualidade fisiológica de mamões e efeito in vitro do extrato da alga marinha Ascophyllum nodosum sobre o fungo Colletotrichum sp. - Dias, Larisse Raquel Carvalho (2019)
The papaya (Carica papaya), belongs to the family Caricaceae, its production takes place throughout the year, highlighting its social importance, by maintaining the generation of employment and continuously income. However, phytosanitary problems negatively affect productivity. In post-harvest, the anthracnose caused by species of the fungus Colletotrichum stands out as one of the most important diseases for the crop. Aiming to establish a natural control method as an alternative for the agroecological management of the disease, the resistance inducing effect of the seaweed Ascophyllum nodosum extract will be evaluated, in different doses, on the parasitism of Colletotrichum sp. in papayas, in post-harvest conditions. We will obtain the isolates for the execution of the tests from symptomatic fruits present in commercial orchards distributed in the Island of São Luís, MA and the tests will consist of two steps. In the first one, the direct effect of the extract on the fungus will be verified. In this sense, in vitro tests, to evaluate the fungistatic effect of the product and the interference of the extract on the permeability of the plasma membrane of the hypha, will be performed. The second stage of the project aims to observe and determine if the algae extract has the potential to induce resistance in papaya. Thus, the fruits will be treated with different concentrations of the product, inoculated with the fungus and daily accompanied to observe the severity of the possible lesions formed. At the end of the experiment that will evaluate the severity of the disease in the treated fruits, the papaya peels will be removed, lyophilized and destined to the biochemical analyzes. In this phase, the project aim to total protein content of the plots, enzyme activity of catalase, guaiacol peroxidase and polyphenoloxidase. The A. nodosum extract, in the in vitro tests, did not inhibit the mycelial growth of the fungus, but the higher doses used negatively influenced the sporulation and germination of the pathogen. Although the extract had no effect against the severity of Colletotrichum sp. in the fruits, presented an eliciting effect for peroxidase and polyphenoloxidase, and also showed no influence on the post harvest quality of the fruits and still delayed the ripening process at 1%, as revealed in the chemical analyzes.